Efeito do camu-camu microencapsulado e liofilizado na reologia da massa e na qualidade do pão de forma - Dionizio, Amanda Salgado (2017)
The camu-camu (Myrciaria dubious H. B. K. (McVaugh)) is a native fruit of the Amazon region, recognized by a high content of vitamin C, source of phenolic compounds, anthocyanins and antioxidants. Due to their potential ascorbic acid, studies are conducted with the objective of adding value to fruit as a food additive. Therefore, the present work has the purpose of evaluating the use of microencapsulated and lyophilized camu-camu pulp in the technological characteristics of wheat flour and in the quality of bread form, by the methods of physicalchemical characterization and microencapsulation of pulp, evaluation (25 and 45ºC), the effect of the lyophilized and microencapsulated in the properties of the flour, the specific volume and the sensorial attributes of the bread of form. The camu-camu pulp presented high levels of ascorbic acid, total phenolic compounds and antioxidant activity. The lyophilizate contains higher moisture content, hygroscopicity and bioactive compounds compared to microencapsulated ones. With the analysis of the efficiency of the encapsulation, maltodextrine was found to be the most efficient for yield, lactate dextrin obtained higher value of phenolic compounds and maltodextrin of ascorbic acid. The stability remained higher at 25 °C, however analyzing both temperatures, lactate dextrin, proved to be the best protective material. The presence of camu - camu caused changes in the characteristics of wheat flour, but the gluten network of the mass was strengthened, making the pasta shorter in relation to the control. The breads did not differ sensorially, except in the attribute appearance and intention to buy the bread with camu - camu microencapsulated with dextrin lactate that was the one with the highest score and the one preferred by the evaluators. The addition of the camu - camu derivatives in the breads provoked an increase in their specific volumes, the bioactive compounds and the retention of ascorbic acid in the final product.